2013
DOI: 10.2147/rrn.s41280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the neonatal intensive care unit environment on preterm infant oral feeding

Abstract: Objective To examine the effect of neonatal intensive care unit environmental characteristics (perceived levels of light and sound, and time of day) in open unit wards and single-family rooms (SFRs) on oral feeding outcomes in preterm infants. Design Data were collected at each scheduled oral feeding for 87 preterm infants from the first oral feeding until discharge. Data included the prescribed volume of feeding and the volume consumed, the infant’s level of wakefulness before feeding, and the nurse’s perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 26 publications
3
22
0
2
Order By: Relevance
“…2 The impact of neonatal morbidities on the transition from full tube to independent oral feeding has been well documented. 2,4,11,[13][14][15] demonstrated that infants with younger gestational ages at birth and higher neonatal morbidity scores took longer to transition from first to independent oral feeding. Park et al (2015) demonstrated that advancement to oral feeding was significantly delayed for infants born at less than 28 weeks' gestation as well as those with morbidities, including neurological injury, BPD, NEC, and patent ductus arteriosus.…”
mentioning
confidence: 99%
“…2 The impact of neonatal morbidities on the transition from full tube to independent oral feeding has been well documented. 2,4,11,[13][14][15] demonstrated that infants with younger gestational ages at birth and higher neonatal morbidity scores took longer to transition from first to independent oral feeding. Park et al (2015) demonstrated that advancement to oral feeding was significantly delayed for infants born at less than 28 weeks' gestation as well as those with morbidities, including neurological injury, BPD, NEC, and patent ductus arteriosus.…”
mentioning
confidence: 99%
“…32 Niveles altos de iluminación han sido asociados a resultados clínicos negativos: menor ganancia de peso, comportamentales y alteraciones en el desarrollo del sueño, además de estrés en pacientes muy prematuros o gravemente enfermos. 7,24,[33][34][35] El cambio brusco en la cantidad de luz también afecta al neonato: Shogan y Schumann 36 reportaron caídas rápidas de saturación en grandes prematuros al aumentar de manera repentina la iluminación. Los neonatos más prematuros son visualmente más vulnerables: se fatigan con facilidad, tienen los párpados muy delgados y su inmadurez les impide cerrar los ojos consistentemente, por lo que son limitados sus recursos de protección frente a la luz.…”
Section: Efectos De La Luz Sobre La Fisiología Y El Desarrollo Del Neunclassified
“…62 Estudios en animales demostraron lesiones de la retina luego de una exposición a luces extremadamente brillantes durante períodos prolongados, algo no practicado, por lo general, en una UCIN. 10,33,63,64 El interés por la luz fue reavivado tras el trabajo de Glass y colaboradores, 65 que reportaron una reducción en la incidencia de ROP al disminuir la iluminación en la UCIN. En busca de dar una respuesta definitiva acerca del efecto de la luz en la ROP, se condujo un estudio multicéntrico aleatorizado denominado LIGHT-ROP, que no encontró diferencias significativas en la gravedad de ROP entre neonatos expuestos y no expuestos a la luz.…”
unclassified
“…32 High lighting levels have been associated with adverse clinical outcomes: less weight gain, behavioral and sleep disturbances, in addition to stress in very preterm or seriously ill patients. 7,24,[33][34][35] A sudden change in the amount of light also affects the newborn infant: Shogan and Schumann 36 reported rapid saturation declines in preterm infants after a sudden increase in lighting. Preterm newborn infants are visually more vulnerable: they get tired easily, have very thin eyelids and their immaturity prevents them from closing their eyes consistently, so they have limited resources for protection from light.…”
Section: Effects Of Light On the Newborn Infant Physiology And Develomentioning
confidence: 99%
“…62 Animal studies showed injury to the retina after exposure to extremely bright lights for long periods, something that is not usually practiced in a NICU. 10,33,63,64 Interest in lighting was revived after the work by Glass and his colleagues, 65 who reported a ROP incidence reduction by lowering lighting in the NICU. Searching for a definitive answer about the effect of light on ROP, a multicenter randomized study called LIGHT-ROP was conducted.…”
mentioning
confidence: 99%